Recent Biotechnology Advances in Bio-Conversion of Lignin to Lipids by Bacterial Cultures - Wang, Huan; Peng, Xiaodong; Li, Hu; Giannis, Apostolos; He, Chao (Frontiers in Chemistry, 2022)
The complexity and recalcitrance of the lignin structure is a major barrier to its efficient utilization and commercial production of high-value products. In recent years, the “bio-funneling” transformation ability of microorganisms has provided a significant opportunity for lignin conversion and integrated biorefinery. Based on the chemical structure of lignin, this mini-review introduces the recent advances of lignin depolymerization by bacterial strains and the application of microbial lignin degradation in lipids production. Furthermore, the current challenges, future trends and perspectives for microbe-based lignin conversion to lipids are discussed.